Killing Patton [compact disc, unabridged] : the strange death of World War II's most audacious general - O'Reilly, Bill (Macmilan, Inc., 2014)
General George S. Patton, Jr. died under mysterious circumstances in the months following the end of World War II. For almost seventy years, there has been suspicion that his death was not an accident, and may very well have been an act of assassination. The audio book looks at the final year of the war and recounts the events surrounding Patton's tragic demise, naming names of the many powerful individuals who wanted him silenced.